Relationship between water imbibition and grain hardness to grain mould resistance in sorghum - S. INDIRA, R.B. SOMANI* and (Indian Phytopathology, 2002)
The relationship between water imbibition and grain hardiness to grain mould resistance was studied in 16 sorghum genotypes. Water imbibition at 30â„ƒ was greater in susceptible sorghum genotypes during the first two hours and then increased many fold, whereas, water imbibition was comparatively less during the first two hours in resistant genotypes, and then increased steadily with time. Seed hardness was measured by breaking strength (kg/cm2). It was observed that some coloured grain genotypes with a more floury endosperm were brittle and with a considerably lower breaking strength. Genotypes requiring more than 5 kg strength for breaking the kernels exhibited good resistance to grain moulds [unspecified] except for CSH1.